Influence of acacia tortilis trees on the distribution of panicum maximum and digitaria macroblephara in South Central Kenya. - Maranga, E.K. (Texas A&M University, 1984)
Water relations of Panicum maximum under Acacia tortilis and Digitaria macroblephara in the open, were studied under field conditions at the National Range Research Station, Kiboko Kenya and under controlled environmental conditions at Texas A&M, University. Mean soil water potentials at 10 cm, 30 cm and 90 cm were significantly lower under Panicum maximum than Digitaria macroblephara. Leaf to air vapor pressure gradients and air temperatures were greater over Digitaria macroblephara than Panicum maximum. Change in temperature increases were higher for Panicum maximum than Digitaria macroblephara. Quantum flux over Digitaria macroblephara and Panicum maximum was 1069~Em -2s-1 and 537~Em-2s-1, respectively. Seasonal transpiration and leaf conductance to water vapor remained higher for Digitaria macroblephara than Panicum maximum. Leaf water potentials were generally lower for Panicum maximum. Increases in transpiration corresponded with increases in stomatal conductance. Transpiration for both species decreased with increase in leaf to air temperature differentials and increase in leaf to air vapor pressure gradients. Digitaria macroblephara had a higher leaf conduc¬tance to water vapor than Panicum maximum for the same leaf temperature. Under conditions of non-limiting water supply in the growth ,chamber, Panicum maximum exhibited higher leaf temperatures and leaf to air saturation vapor pressures. Under moisture stress, Panicum maximum experienced lower leaf water potentials and reached wilting stage faster than Digitaria macroblephara. These differences may be due in part to morpho¬logical variations. As the plants became drier, diffusive resistance increased for both species with a steeper decline in Panicum maximum than Digitaria macroblephara. Leaf tempera¬tures departed little between the species; however, a degree change in leaf temperature was associated with a greater change in leaf water potential for Panicum maximum than Digi¬taria macroblephara. Based on the results of this study, it is possible to conclude that the distribution of Panicum maximum and Digintaria macroblephara reflect ecological differences arising from microclimatic modification induced by Acacia tortilis.